The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/ajr.12214
|View full text |Cite
|
Sign up to set email alerts
|

Birthing in rural South Australia: The changing landscape over 20 years

Abstract: This study has revealed that almost one quarter of all women residing in rural South Australia relocate to another area to give birth. This is a significant concern for rural women and their families through the expectation of separation, and for the local health services who might now not have the facilities and skills to manage an unplanned maternity presentation. These concerns need to be considered and addressed in order to provide safe and effective care for child-bearing women regardless of location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
(18 reference statements)
1
16
0
Order By: Relevance
“…We found that on-call and scope-of-practice arrangements were diverse and adapted Local arrangements for collaboration, referral and backup differed markedly depending on a the presence of a critical mass of GPOs, GP anaesthetists, midwives and theatre staff -a critical mass that has been eroded resulting in the closure of rural maternity units across Australia. 10 Recently efforts have been made…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that on-call and scope-of-practice arrangements were diverse and adapted Local arrangements for collaboration, referral and backup differed markedly depending on a the presence of a critical mass of GPOs, GP anaesthetists, midwives and theatre staff -a critical mass that has been eroded resulting in the closure of rural maternity units across Australia. 10 Recently efforts have been made…”
Section: Discussionmentioning
confidence: 99%
“…Local arrangements for collaboration, referral and backup differed markedly depending on a the presence of a critical mass of GPOs, GP anaesthetists, midwives and theatre staff – a critical mass that has been eroded resulting in the closure of rural maternity units across Australia. 10 Recently efforts have been made to halt this trend, and so to enable more rural women to deliver locally, surrounded by family. 4…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Reduced availability of these services is likely to among the major discrepancies for women in rural areas. 6,7,12,[18][19][20] Increasing access to specialist care is not a simple task or a solution that will likely be achieved in the short-term. [20][21][22] In the meantime, investment in initiatives such as telehealth appears to be one avenue for improved outcomes.…”
Section: Previous Work Bymentioning
confidence: 99%
“…International goals and rigorous audit remain relevant to maternity units of all sizes, including small rural units . While modern transport and communications go some way to bringing health care to rural and remote Australia, disparate health outcomes still exist in maternal and infant health …”
Section: Background and Rationale For Reviewmentioning
confidence: 99%